Barnperspektiv i barnfridsbrott - en studie av de första domarna från Skånes tingsrätt - Holmqvist,Toini (2025)
This study examines the child perspective in court rulings regarding domestic violence offences affecting children in Skåne from July 2021 to June 2022. The research aims to analyze how children's voices and experiences are presented in these rulings (documents), identify if children are recognized as victims, and what compensation they receive. The research employs a quantitative and qualitative content analysis of court rulings as a method, enabling a detailed exploration of the textual content of the rulings concerning children's experiences and legal handling. Theoretically, the study connects to the concepts of child perspective as ideological and methodological tools, which help distinguish between adults' interpretations and children's perspectives. Results show that children often appear as indirect victims in judicial documents, and their stories are primarily conveyed through adult witnesses or video recordings from interviews, which may limit the representation of their actual experiences. Furthermore, the compensation to children varies, and considerable emphasis is placed on the child's age and maturity in legal assessments. The conclusion is that although children are recognized as victims, further measures are needed to fully integrate and respect the child’s perspective in the legal process concerning domestic violence offences affecting children. This study underscores the importance of incorporating the child perspective in social work practices to ensure that interventions are sensitive to the unique needs and rights of children affected by domestic violence.
Keywords: child perspective; domestic violence; legal representation; victim compensation